2019
DOI: 10.1177/1010539519889765
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maternal Education and Vaccination Coverage: Evidence From Pakistan Demographic and Health Survey

Abstract: The aim of this study was to examine the impact of maternal education on child immunization uptake in Pakistan, both at individual and community levels. Pakistan Demographic and Health Survey data were used for analysis. Multilevel logistic regression was used to access the individual- and community-level factors associated with childhood immunization coverage. Out of 6765 children 2659 (39.3%) were fully immunized. Parents education, access to media, and wealth status have positive while ethnicity and working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Maternal education is the most important determinant affecting the vaccination inequality followed by wealth status and father's educational level. A recently published study on the matter also showed positive impact on child vaccination coverage both at individual and community level (Asif, Akbar, Tahir, et al, 2019). Moreover, our findings are also consistent with a recently published literature on the issue (Acharya, Paudel, & Dharel, 2019;Asif & Akbar, 2020).…”
Section: Discussionssupporting
confidence: 92%
“…Maternal education is the most important determinant affecting the vaccination inequality followed by wealth status and father's educational level. A recently published study on the matter also showed positive impact on child vaccination coverage both at individual and community level (Asif, Akbar, Tahir, et al, 2019). Moreover, our findings are also consistent with a recently published literature on the issue (Acharya, Paudel, & Dharel, 2019;Asif & Akbar, 2020).…”
Section: Discussionssupporting
confidence: 92%
“…The role of household wealth status has been reported in various studies. 15-19 In this study, children from high household wealth index status were more likely to seek medical care help than children from low household wealth index status. Although the national health insurance system in Indonesia has been implemented in the past 5 years; financial readiness of the community still affects utilization of health care services.…”
Section: Discussionmentioning
confidence: 66%
“…In districts where the validation process was successfully conducted, respondents and children tended to be more educated, work in an office (as opposed to working in a bluecollar job), and have a higher quantity of children aged 9 to 59 months. Several studies have found that the level of education of a mother or carer is an independent factor for higher immunization coverage [35][36][37][38], while a carer working and having more children could decrease coverage [35,36]. In addition, these districts were mainly urban, where the overall uptake of vaccinations tends to be lower than in rural areas [35,39].…”
Section: Limitations Of Immunization Registers At Chcsmentioning
confidence: 99%
“…Several studies have found that the level of education of a mother or carer is an independent factor for higher immunization coverage [35][36][37][38], while a carer working and having more children could decrease coverage [35,36]. In addition, these districts were mainly urban, where the overall uptake of vaccinations tends to be lower than in rural areas [35,39]. To some extent, those factors may indirectly influence the accuracy of an immunization reporting system due to, for example, failure to report immunizations or losing immunization cards [31,37].…”
Section: Limitations Of Immunization Registers At Chcsmentioning
confidence: 99%